2021
DOI: 10.18280/ijht.390211
|View full text |Cite
|
Sign up to set email alerts
|

Dual Entropy Regime in Channel Flow Subjected to Temperature Dependent Convection Mechanism

Abstract: The central stimuli of this brief note is to underscore the effect of the temperature dependent convection coefficient that give rise to a dual temperature regime facilitating dual entropy distribution. In order to avoid unwarranted complexities, a simple geometry of shear flow in a channel is considered. The energy equation amenable to an analytic solution is simulated to extract the desired numerical findings in as much as for what parameters’ values, the temperature has dual distribution /does not yield tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Obalalu et al [26] investigated the heat transfer enhancement on the thermodynamics process of an unsteady Newtonian fluid with the existence of a convective heating effect. The entropy generation and hydrodynamic slip of hybrid nanofluid with temperature-dependent convection were studied by [27]. A mathematical model namely Optimal Homotopy Analysis Method (OHAM) was established by [28] to study the nanofluid of entropy generation and thermal conductivity of natural convective.…”
Section: Nomenclaturementioning
confidence: 99%
“…Obalalu et al [26] investigated the heat transfer enhancement on the thermodynamics process of an unsteady Newtonian fluid with the existence of a convective heating effect. The entropy generation and hydrodynamic slip of hybrid nanofluid with temperature-dependent convection were studied by [27]. A mathematical model namely Optimal Homotopy Analysis Method (OHAM) was established by [28] to study the nanofluid of entropy generation and thermal conductivity of natural convective.…”
Section: Nomenclaturementioning
confidence: 99%
“…Realizing the potential of the field, many investigators have reported entropy analysis for a variety of fluidic systems. [18][19][20][21][22][23][24][25][26][27][28][29][30] We recall that the Fourier heat fluxlaw 31 falls short to address heat transport taking place in the waveform. Cattaneo 32 proposed a modification suggesting the inclusion of time relaxation component thermal inertia to Fourier's heat flux model.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the entropy generation analysis banking upon picking up parameters having a qualitative and quantitative impact on entropy production is pivotal in entropy minimization. Realizing the potential of the field, many investigators have reported entropy analysis for a variety of fluidic systems 18–30 …”
Section: Introductionmentioning
confidence: 99%
“…Several findings have established nanofluids to possess not only higher thermal conductivity than the host fluids., but to generate an enhanced frictional pressure drop. Meanwhile, nanotechnology has become one of the emerging researchable solutions in heat pipes, sensors, micro/mini channels, clean energy devices, heat sinks, composite materials, automobiles, medicine, cosmetic, airconditioning and refrigeration, solar energy device, lubricants, and coolants applications through the suspension of ultrafine nano-dimensioned (<100 nm) solid particles to enhance the thermo-physical characteristic of the base fluid matrix [2][3][4]. The challenges with micrometer-dimensioned solid particles includes abrasion, sedimentation, and the risk of clogging, whereas the unique quality of nanofluids for various desirable utilization includes its excellent heat conductivity, heat transfer capability, stability, friction coefficient, erosion reduction and lubrication.…”
Section: Introductionmentioning
confidence: 99%